2019
DOI: 10.31089/1026-9428-2019-59-8-452-457
|View full text |Cite
|
Sign up to set email alerts
|

Working conditions and occupational pathology of coal miners in the Arctic

Abstract: Introduction. Due to the impact of adverse working conditions and climate, workers in coal-mining enterprises in the Arctic are at increased risk of occupational diseases (OD).The aim of the study was to study the working conditions, causes, structure and prevalence of occupational diseases in miners of coal mines in the Arctic.Materials and methods. Th e data of social and hygienic monitoring “Working conditions and occupational morbidity” of the population of Vorkuta and Chukotka Autonomous District in 2007–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
0
1
0
7
Order By: Relevance
“…The present work quite logically revealed that more than 80 % occupational pathology cases were detected among miners. Occupational pathologies were similarly distributed as per economic activities in other Arctic regions with developed mining industry such as Murmansk region, polar zones in Krasnoyarsk region, and Komi Republic [5,14,15]. It is well-known that it is prohibited to employ women at mining enterprises or mines or their labor is strictly limited at such industrial objects 4 .…”
mentioning
confidence: 99%
“…The present work quite logically revealed that more than 80 % occupational pathology cases were detected among miners. Occupational pathologies were similarly distributed as per economic activities in other Arctic regions with developed mining industry such as Murmansk region, polar zones in Krasnoyarsk region, and Komi Republic [5,14,15]. It is well-known that it is prohibited to employ women at mining enterprises or mines or their labor is strictly limited at such industrial objects 4 .…”
mentioning
confidence: 99%
“…Введение. Здоровье работающего населения является необходимым условием повышения производительности труда и экономического развития 1 , с одной стороны, и качества жизни самих работников -с другой. Время, проведенное на рабочем месте, занимает существенную часть временного бюджета современного человека.…”
unclassified
“…Данный факт обусловливает актуальность изуче ния отдельных факторов здоровья трудящегося населения на рабочем месте, важнейшими из которых являются условия и характер труда. Согласно Трудовому кодексу РФ, под услови ями труда понимают совокупность факторов производственной среды и трудового процесса, 1 Здоровье работающих: глобальный план действий: Шестидесятая сессия Всемирной ассамблеи здравоохранения. 23 мая 2007 года [Электронный ресурс] // Всемирная организация здравоохранения.…”
unclassified
See 2 more Smart Citations